Unsaturated soil mechanics in geotechnical practice - Blight, G. E. (Boca Raton : CRC Press, 2013)
"Soil will, either seasonally or occasionally, pass from the unsaturated to the saturated state and even from unsaturation to dryness. The theory of unsaturated soils is dealt with, including its application to natural undisturbed soils and compacted soils. Application of the theory to soil-like materials such as mine waste and municipal solid waste is also covered. Application of the theory to practice is illustrated by a number of detailed case histories. Unsaturated soil mechanics principles can also successfully and usefully be applied in related fields such as the bulk storage of particulate materials, underground mine support, solution mining and concrete structures"--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Soils -- Testing; Soil moisture -- Measurement; Soils -- Plastic properties; Zone of aeration; Electronic books